1980
DOI: 10.1159/000155943
|View full text |Cite
|
Sign up to set email alerts
|

Habitat Quality and Populations of Two Sympatric Gibbons (Hylobatidae) on a Mountain in Malaya

Abstract: Sympatric gibbon species Hylobates lar and H. syndactylus were censused on a mountain in Malaya (West Malaysia). Habitat quality was assessed between 380- and 1,525-m altitudes. H. syndactylus was found to occur up to altitudes higher than does H. lar, and this is discussed with reference to the two species’ divergent foraging strategies indicated by previous research. It is suggested that gibbons are restricted in their altitudinal range by an increasingly unfavourable ratio of food consumed to energy expende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 7 publications
0
24
0
Order By: Relevance
“…Elevational range of primates can be further constrained by reduced food density at high elevations (Durham, 1975;Caldecott, 1980). Diversity, basal area and proportion of food trees, are all correlated with lar gibbon biomass (Caldecott, 1980). The same study indicated a switch to less favorable food species at high elevation.…”
Section: Elevational Effectsmentioning
confidence: 87%
See 1 more Smart Citation
“…Elevational range of primates can be further constrained by reduced food density at high elevations (Durham, 1975;Caldecott, 1980). Diversity, basal area and proportion of food trees, are all correlated with lar gibbon biomass (Caldecott, 1980). The same study indicated a switch to less favorable food species at high elevation.…”
Section: Elevational Effectsmentioning
confidence: 87%
“…Caldecott (1980) suggested that the ratio between energy expenditure and nutrient intake becomes unfavourable for Malayan gibbons at high elevation, which is attributed to the increased costs of thermoregulation and locomotion in cool and tangled habitats. Elevational range of primates can be further constrained by reduced food density at high elevations (Durham, 1975;Caldecott, 1980). Diversity, basal area and proportion of food trees, are all correlated with lar gibbon biomass (Caldecott, 1980).…”
Section: Elevational Effectsmentioning
confidence: 99%
“…They also found some weak indication that the probability of occupancy may in crease with tree diversity. Tree diversity has been found to be an important habitat requirement of gibbons (Caldecott 1980, Fan & Jiang 2008, Phoonjampa et al 2010. Low tree-species diversity in the survey areas indicates that some inter-group resource competition may occur and that the probability of gibbon occupancy increases in areas of high tree diversity (Mitani 1985, Brockelman & Srikosamatara 1993, Nijman 2004, Fan et al 2009).…”
Section: Fixed-point Triangulationmentioning
confidence: 96%
“…It follows that these reductions could result in corre sponding reductions in the presence and abundance of large bodied frugivores, such as primates. Indeed a reduction in numbers of primates at higher elevations has been re ported in several previous studies (Caldecott 1980, Marshall et al 2005, including spider monkeys (Durham 1975) and is commonly attributed to the increased energetic costs of finding sufficient food as a result of lower densities and reduced quality of resources (Wrangham et al 1993, Marshall et al 2005, and in the case of folivores on lower quality, less digestible food as a result of en vironmental conditions at high elevation sites (Marshall et al 2005).…”
Section: Discussionmentioning
confidence: 89%